A novel heterozygous missense mutation in the UMOD gene responsible for Familial Juvenile Hyperuricemic Nephropathy - Calado, Joaquim (2017)
Background: Familial Juvenile Hyperuricemic Nephropathy is an autosomal dominant nephropathy, characterized by decreased urate excretion and progressive interstitial nephritis. Mutations in the uromodulin coding UMOD gene have been found responsible for the disease in some families. Case presentation: We here describe a novel heterozygous p. K307T mutation in an affected female with hyperuricemia, renal cysts and renal failure. The proband's only son is also affected and the mutation was found to segregate with the disease. Conclusions: This mutation is the fourth reported in exon 5. Initial studies identified a mutation clustering in exon 4 and it has been recommended that sequencing this exon alone should be the first diagnostic test in patients with chronic interstitial nephritis with gout or hyperuricemia. However, regarding the increasing number of mutations being reported in exon 5, we now suggest that sequencing exon 5 should also be performed.